1972
DOI: 10.1111/j.1469-185x.1972.tb00969.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐chromosome Inactivation and Developmental Patterns in Mammals

Abstract: Summary 1. The review considers information from mammalian embryology relevant to X‐chromosome inactivation, and from X‐inactivation relevant to mammalian embryology. 2. Properties of the inactive‐X, by which it may be recognized are: sex chromatin, heteropycnosis, late replication and the absence of gene product. Each of these has advantages and disadvantages in particular circumstances. In some species the X carries constitutive heterochromatin, which must be distinguished from the facultative region. 3. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
175
0
3

Year Published

1979
1979
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 624 publications
(179 citation statements)
references
References 172 publications
1
175
0
3
Order By: Relevance
“…This difference in gene dosage is "compensated" in mammals and in Drosophila, so that males and females produce equal amounts of enzymes from such sex-linked genes. In male Drosophila compensation is achieved by transcription of X-linked genes at twice the female rate (Lucchesi, 1973); in mammals, one of the X-chromosomes in every somatic cell of the female is inactivated, so that females have the same effective gene dose as males (Lyon, 1972). Neither of these mechanisms has been demonstrated to occur in other organisms.…”
Section: Introductionmentioning
confidence: 99%
“…This difference in gene dosage is "compensated" in mammals and in Drosophila, so that males and females produce equal amounts of enzymes from such sex-linked genes. In male Drosophila compensation is achieved by transcription of X-linked genes at twice the female rate (Lucchesi, 1973); in mammals, one of the X-chromosomes in every somatic cell of the female is inactivated, so that females have the same effective gene dose as males (Lyon, 1972). Neither of these mechanisms has been demonstrated to occur in other organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Such analysis in rodent livers suggests that hepatocytes randomly allocate their progeny in liver development and regeneration (Iannaccone et al, 1987;Khokha et al, 1994;Ng and Iannaccone, 1992). We have immunohistochemically demonstrated that, in spf ash (sparse-fur with abnormal skin and hair)-heterozygous mouse liver (DeMars et al, 1976;Hodges and Rosenberg, 1989;Ohtake et al, 1987), ornithine transcarbamylase (OTC) expression is mosaic in hepatocytes because of the random inactivation of either the X chromosome carrying the spf ash gene or the wild-type gene (Lyon, 1961(Lyon, , 1972Wareham and Williams, 1986), and that the mosaic pattern can be analyzed in both two and three dimensions (Shiojiri et al, 1997). Analysis of the OTC mosaic pattern in the fetal mouse liver, where biliary cell differentiation occurs, may be helpful in resolving the issues mentioned above.…”
mentioning
confidence: 92%
“…In mammals, dosage compensation is achieved by inactivation of one of the X-chromosomes in the somatic cells of the female (the homogametic sex), so equalising the gene dose in males and females (Lyon, 1972). In Drosophila, an alternative mechanism of dosage compensation (dosage compensation sensu strictu) has evolved, whereby the effective dose of X-linked genes is equalised in the two sexes by an increased rate of transcription in the male (Lucchesi, 1973).…”
Section: Introductionmentioning
confidence: 99%